Relevansi Konsep Pendidikan Islam Perspektif KH. Hasyim Asy’ari Pada Era Modern - Ory Syafari Jamel Sutiyan; Asep Saeful Bahri; Zaenal Abidin; Dolly Riri Ramdhanu Jamel Sutiyan; Fitri Mutmainnah (Departement of Mathematics Education, 2023)
The development of the times is a challenge that cannot be avoided. At present, the development of the world of education is in the spotlight. Educators' reduced aesthetic and moral values are particular problem that must be faced. In this case, the thoughts of the nation's teacher, KH Hasyim Asy'ari, try to provide answers and conceptions that can answer the problem and are still relevant for use in the current era. The type of research used in this study is qualitative descriptive research, and the type of classification of this research is based on research technical literature; the data studied is in the form of books and literature sourced from literature. The results of this study are the relevance of Islamic religious thought in education according to KH Hasyim Asy'ari with the changes and developments of this era that Islamic education has the goal of increasing the degree of piety to God and creating or arousing a productive and dynamic human spirit on the right path.